Investigation of Adsorption of Gluconic Acid from Aqueous Solutions by Activated Carbon - INCI, ISMAIL (Asian Journal of Chemistry, 2010)
The separation of gluconic acid from aqueous solutions using activated carbon was examined. Experiments were carried out in the system of aqueous gluconic acid solutions (0.75, 1.5, 3, 5 and 8%, w/w) and different amounts of activated carbon (0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007 and 0.008 g) as adsorbent. The equilibrium distributions of gluconic acid were measured. Adsorption experiments were carried out at 298 K. The adsorption of gluconic acid was found to be appreciable in activated carbon. The percentage removal of gluconic acid was 94.14%. The equilibrium data fit well within the Freundlich isotherms.